Left ventricular fibromas in pediatric patients: a case series and review of the literature - Chun Zhou; Jia Liu; Shoujun Li; Huiying Wang; Yu Jin; Jinping Liu (Journal of Cardiothoracic Surgery)
Abstract Cardiac fibromas are rare benign primary tumors of the heart; nearly one-third of affected patients are less than 1 year old, and only 15% of patients develop this disease in adulthood. Here, we report three cases of cardiac fibroma in our hospital. In all the patients, the cardiac mass was diagnosed using cardiac imaging, namely CT and MRI scans. The tumors were surgically resected under cardiopulmonary bypass, and the fibroma was diagnosed by histopathology and microscopy. The cardiac function of the three pediatric patients recovered after the operation, and the patients were discharged successfully.